2012
DOI: 10.1186/1546-0096-10-24
|View full text |Cite
|
Sign up to set email alerts
|

A comparative proteomic study of sera in paediatric systemic lupus erythematosus patients and in healthy controls using MALDI-TOF-TOF and LC MS–A pilot study

Abstract: BackgroundPaediatric systemic lupus erythematosus (pSLE) exhibits an aggressive clinical phenotype with severe complications and overall poor prognosis. The aim of this study was to analyse differential expression of low molecular weight (LMW) serum protein molecules of pSLE patients with active disease in comparison to sera of healthy age matched controls. Further, some of the differential expressed spots were characterised and identified by Matrix Assisted Laser Desorption Ionization Time of Flight Mass Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…It has been associated with numerous disorders including, familial amyloid cardiomyopathy and senile systemic amyloidosis . A pilot study showed that transthyretin levels were upregulated in the sera of paediatric SLE patients compared to healthy controls . Additionally, increased serum levels of transthyretin were associated with the severity of rheumatoid arthritis, suggesting a role in disease pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…It has been associated with numerous disorders including, familial amyloid cardiomyopathy and senile systemic amyloidosis . A pilot study showed that transthyretin levels were upregulated in the sera of paediatric SLE patients compared to healthy controls . Additionally, increased serum levels of transthyretin were associated with the severity of rheumatoid arthritis, suggesting a role in disease pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Another down-regulated protein identified is TTR, which is a serum and cerebrospinal fluid transporter of the thyroid hormone thyroxine (T4), and of retinol ( Zheng et al, 2001 ). Earlier proteomic observations by Rana et al showed the increased expression of TTR in serum obtained from pediatric SLE patients compared to controls ( Rana et al, 2012 ). In our proteomic study, we have identified TTR reduced expressions in adult SLE patients.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies on PV serum proteomic MS have provided a scientific basis for the pathogenesis of PV ( 10 – 12 ). However, there is a possibility that the proteins at high abundance in the samples may affect the detection of those at low abundance.…”
Section: Discussionmentioning
confidence: 99%